Carbonos no material ativo de baterias chumbo-ácido - Tsurumaki, Maumi (Universidade Federal de São Carlos, 2015)
Different types of carbon has been studied globally as additives for negative active material of lead acid batteries aiming to improve the charge acceptance and the cycling endurance of the batteries when applied in PSoC (Partial State of Charge) condition of start stop application. This study focused in the carbon black and graphite available in the market. It has been developed a laboratory method to produce the negative plates and then cells of type “p/n/p” has been assembled for characterization of negative plates produced in the laboratory. In the first part of the study it was observed the physical effects caused by addition of different amounts of carbon in the lead oxide paste which compounds the negative plate of the battery. It has observed in the experiments that higher the amount of carbon added in the lead oxide, more amount of water needed to produce the lead oxide paste in the plastic region. In the second part of the study it was verified the influence of carbon black or graphite addition in the electrochemical performance of negative plates. The plates produced with addition of 0.2 % of carbon black, or 2.0 % of graphite presented the plate capacity in mA h g-1 in the Peukert’s representation very similar to the plates of serial production from market. In the case of the plates produced with addition of 0.2 % of graphite, the test resulted in lower capacity in mA h g-1 in Peukert’s representation, very close to the plates produced without carbon addition. In the charge and discharge endurance test in PSoC condition, the plates produced in the laboratory with addition of 0.2 % of carbon black or 2.0 % of graphite presented better potential stability measured in V/cycle if compared to the plates of serial production from market or even plates produced with addition of only 0.2 % of graphite. These data signs to estimation of higher number of cycles until the end of life of the negative plates produced with 0.2 % of carbon black or 2.0 % of graphite, showing the beneficial effects of carbons in the negative active material of lead acid battery.
Keywords: Carbono; Baterias chumbo-ácido; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA